2008
DOI: 10.1080/10934520801974418
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of phenanthrene from contaminated kaolinite by electroremediation-Fenton technology

Abstract: Polycyclic aromatic hydrocarbons (PAHs) cause a high environmental impact when released into the environment. The objective of this study was to evaluate the capacity to decontaminate polluted soils with phenanthrene as a model PAH using a combination of two technologies: electrokinetic remediation and Fenton process. Kaolinite was used as a model sample that was artificially polluted at the laboratory at an initial concentration of phenanthrene of 500 mg kg(-1) of dried kaolinite. The standard electrokinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Kim et al [40] utilized 7% H 2 O 2 and 0.01 N H 2 SO 4 in the anode chamber in the EKFenton treatment of kaolin polluted with phenanthrene. On the other hand, the effectiveness of the EK-Fenton technique to treat soils contaminated with PAHs has been proved by Alcá ntara et al [12]. They found that when anode and cathode chambers were filled with H 2 O 2 (10%) the overall removal and a destruction efficiency of phenanthrene of 99% were obtained in 14 days.…”
Section: Ek-fenton-edta Remediationmentioning
confidence: 95%
See 1 more Smart Citation
“…Kim et al [40] utilized 7% H 2 O 2 and 0.01 N H 2 SO 4 in the anode chamber in the EKFenton treatment of kaolin polluted with phenanthrene. On the other hand, the effectiveness of the EK-Fenton technique to treat soils contaminated with PAHs has been proved by Alcá ntara et al [12]. They found that when anode and cathode chambers were filled with H 2 O 2 (10%) the overall removal and a destruction efficiency of phenanthrene of 99% were obtained in 14 days.…”
Section: Ek-fenton-edta Remediationmentioning
confidence: 95%
“…A substantial list of applications of electroremediation for the elimination of metals and some undesirable inorganic anions such as fluoride exists in the bibliography [3][4][5][6][7]. Also, in recent years several research groups have begun to analyze the application of this technology to soils contaminated by organic compounds, such as polycyclic aromatic hydrocarbons (PAHs) and benzene, toluene, ethylbenzene, and xylenes (BTEX) [8][9][10][11][12][13][14], phenol [15], organochlorates [16], trichloroethelene and tetrachloroethane [17] and dyes [18].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the effectiveness of the Electro-Fenton technique to treat soils contaminated with PAHs has been proved by Alcántara et al [74]. They found that when anode and cathode chambers were filled with H 2 O 2 (10%), the kaolin pH is maintained at an acid value around 3.5 without pH control and an overall removal and destruction efficiency of phenanthrene of 99% was obtained in 14 days.…”
Section: Electro-fentonmentioning
confidence: 94%
“…Several studies [19,20,34,35], along with the authors' previous study [21], have reported that electrokinetic treatment can be combined with the Fenton reaction (EK-Fenton) to promote the removal of model organic compounds, such as phenanthrene or trichloroethylene. Based on these studies, a new experiment was developed with the aim of achieving total remediation of diesel fuel polluted soil (see Tab.…”
Section: Electrokinetic Treatment With the Fenton Reactionmentioning
confidence: 99%
“…The Fenton reaction involves two steps: first, the decomposition of H 2 O 2 , which is catalyzed by Fe(II) and results in the generation of hydroxyl radicals, and, secondly, the degradation of organic pollutants by hydroxyl radicals via oxidation [19]. This technology has been used for the remediation of phenanthrene in a model soil such as kaolin [20,21] or mixture of sand and bentonite [22]. So far, only Tsai et al [23] have used this technology to remediate diesel fuel contaminated soil.…”
Section: Introductionmentioning
confidence: 99%